Image-Based Framework for Concrete Surface Crack Monitoring and Quantification - ZhiQiang Chen; Tara C. Hutchinson (Advances in Civil Engineering)
In the engineering community, nondestructive imaging has been widely used for damage identification by capturing anomalies on the surface or inside of structural elements. In this paper, we focus on one of the most common damage types observed in civil engineering, namely, concrete surface cracks. To identify this type of damage, we propose an image-based framework, whereby optical cameras provide the source images. The framework involves several advanced image processing methods, including: (i) the determination of damage occurrence using time-series images, (ii) the localization of damage at each image frame, and (iii) the geometric quantification of damage. Challenges that may arise when images are obtained in the laboratory or field environment are addressed. Two application examples are provided to demonstrate the use and effectiveness of the proposed approach.